Enzyme-microplastic interaction induces oxidative stress in earthworm: molecular docking and toxicity study - Babita Thakur; Jaswinder Singh; Joginder Singh; Deachen Angmo; Hardeep Kaur; Gurpreet Singh; Jatinderpal Singh; Adarsh Pal Vig (Discover Soil)
Abstract Microplastics become a major contaminant in terrestrial ecosystem and induce a negative impact on soil fauna. The main objective of this study was to check the deleterious effects of polypropylene microplastics on exotic earthworm species Eisenia fetida. Earthworms were treated with different concentrations of polypropylene (0, 1000, 4000, 8000, and 16,000 mgkg−1) in artificial soil to know its effect on oxidative stress, biomass and reproduction rate of earthworm. Highest concentrations of polypropylene pose significant negative effects on the biomass and fecundity rate and the effect increases with treatment period. Different antioxidant enzymes (Superoxide Dismutase (SOD), Catalase (CAT), Glutathione-S-Transferase (GST) and Guiacol Peroxidase (POD) activity increase up to 14 days but inhibit the enzymatic activity at 8000 and 16,000 mgkg−1 while POD activity increases with increase in exposure time. The unit activity of different enzymes SOD, CAT and GST on 14th day at 16,000 mgkg−1 is 0.015, 0.074, and 0.097 respectively but on 28th day at similar concentration the unit activity significantly decrease 0.008, 0.058, and 0.045. Highest concentrations of polypropylene i.e. 8000 and 16,000 mgkg−1 were seems to be more relevant for enzyme-interaction with polypropylene. The unit activity of POD enzymes on 7th day at highest concentration (16,000 mgkg−1) is 0.025 and on 28th day at similar concentration the unit activity is 0.035. High concentrations of polypropylene produce oxidative stress on different antioxidant enzymes of E. fetida. Molecular docking study shows the bonding of hydrogen atoms and hydrophobic interactions of PP modulates the activity of all enzymes.